2012
DOI: 10.3389/fpsyg.2012.00566
|View full text |Cite
|
Sign up to set email alerts
|

Face Distortion Aftereffects Evoked by Featureless First-Order Stimulus Configurations

Abstract: After prolonged exposure to a distorted face with expanded or contracted inner features, a subsequently presented normal face appears distorted toward the opposite direction. This phenomenon, termed as face distortion aftereffect (FDAE), is thought to occur as a result of changes in the mechanisms involved in higher order visual processing. However, the extent to which FDAE is mediated by face-specific configural processing is less known. In the present study, we investigated whether similar aftereffects can b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 108 publications
(148 reference statements)
1
7
0
Order By: Relevance
“…For example, Afraz and Cavanagh (2009) argue that face aftereffects show transfer across retinal position, orientation, and size that far exceed the tuning widths of low-level mechanisms early in the processing stream; they argue that their results are consistent with the site of adaptation being the high-level mechanisms that process faces. Similar arguments have been made by many other researchers (e.g., Hills & Lewis, 2012;Hole, 2011;Leopold, O'Toole, Vetter, & Blanz, 2001;Vakli, Németh, Zimmer, Schweinberger, & Kovács, 2012;Watson & Clifford, 2003;Yamashita, Hardy, De Valois, & Webster, 2005;Zhao & Chubb, 2001). On the other hand, Dickinson and Badcock (2013) argue that the transfer across retinal position in these studies may have been mediated by inadvertent eye movements, while transfer across changes in size and orientation could still have been mediated by low-level processes.…”
Section: Introductionsupporting
confidence: 87%
“…For example, Afraz and Cavanagh (2009) argue that face aftereffects show transfer across retinal position, orientation, and size that far exceed the tuning widths of low-level mechanisms early in the processing stream; they argue that their results are consistent with the site of adaptation being the high-level mechanisms that process faces. Similar arguments have been made by many other researchers (e.g., Hills & Lewis, 2012;Hole, 2011;Leopold, O'Toole, Vetter, & Blanz, 2001;Vakli, Németh, Zimmer, Schweinberger, & Kovács, 2012;Watson & Clifford, 2003;Yamashita, Hardy, De Valois, & Webster, 2005;Zhao & Chubb, 2001). On the other hand, Dickinson and Badcock (2013) argue that the transfer across retinal position in these studies may have been mediated by inadvertent eye movements, while transfer across changes in size and orientation could still have been mediated by low-level processes.…”
Section: Introductionsupporting
confidence: 87%
“…In addition, the influence of second-order relations on face discrimination showed a positive correlation with individual face recognition skills (Rotshtein et al, 2007). High-level face aftereffects can be induced by schematic faces lacking all the typical facial features, indicating the role of higher level visual areas in the coding of face configuration (Vakli et al, 2012). Accordingly, functional imaging studies have shown that regions of the fusiform gyrus overlapping with (Goffaux et al, 2009;Rhodes et al, 2009;Rotshtein et al, 2007), or adjacent to face-preferring voxels are sensitive to the spacing of features.…”
Section: Configurationmentioning
confidence: 97%
“…This indicates that the representation of unfamiliar faces is distinct to famous faces, but both share some similiarities with the representation of personally familiar and self faces. Finally, aftereffects in famous faces transfer across viewpoint and photographic negation but not across orientation (Hills and Lewis, 2012;Vakli et al, 2012) indicating the representation of familiar faces is more robust than unfamiliar faces.…”
mentioning
confidence: 91%
“…In one of the most inovative studies in face aftereffects, Vakli et al (2012) have shown that the FDAE can be caused by gray stimuli with white dots in the triangular configuration of the internal facial features. This indicates that higher-level visual areas involved in the processing of facial configurations mediate the FDAE.…”
mentioning
confidence: 99%